2020
DOI: 10.1002/cend.202000017
|View full text |Cite
|
Sign up to set email alerts
|

Planar tomography and numerical analysis for damage characterization of impact loaded RC plates

Abstract: The damage analysis of reinforced concrete (RC) is of high interest for reasons of effective maintenance and structural safety of buildings. The damage structures of RC plates loaded by an impact were investigated, applying X-ray planar tomography and finite element method (FEM). Planar tomography allows getting three-dimensional information of the RC elements and the damage including crack, spalling, and scabbing. The FEM model validated on the tomography data justifies the application for further predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This procedure made it possible to get a view of the damage inside the plates. The shape of the fracture body inside the plate is usually described as a cone [21][22][23], but in our experiments, the shape deviated significantly from a cone, see Figure 8. It was measured by means In comparison to the non-strengthened RC plates, it was found that local damage due to scabbing on the rear side of the RC plate (StrRC_BZT1) was completely prevented by the subsequent applied strengthening layer.…”
Section: Local Damage-punching Shear Failurementioning
confidence: 63%
See 1 more Smart Citation
“…This procedure made it possible to get a view of the damage inside the plates. The shape of the fracture body inside the plate is usually described as a cone [21][22][23], but in our experiments, the shape deviated significantly from a cone, see Figure 8. It was measured by means In comparison to the non-strengthened RC plates, it was found that local damage due to scabbing on the rear side of the RC plate (StrRC_BZT1) was completely prevented by the subsequent applied strengthening layer.…”
Section: Local Damage-punching Shear Failurementioning
confidence: 63%
“…This procedure made it possible to get a view of the damage inside the plates. The shape of the fracture body inside the plate is usually described as a cone [21][22][23], but in our experiments, the shape deviated significantly from a cone, see Figure 8. It was measured by means of digital image analysis.…”
Section: Local Damage-punching Shear Failurementioning
confidence: 63%